Microbial production of mevalonate by recombinant Escherichia coli using acetic acid as a carbon source. Issue 1 (1st January 2018) - Xu, Xin; Xie, Meng; Zhao, Qian; Xian, Mo; Liu, Huizhou
ABSTRACT: We sought to produce mevalonate, an important organic acid, by recombinant Escherichia coli, using acetic acid, a less costly alternative feedstock, as a carbon source. In this study, the mevalonate biosynthesis pathway originating with acetate was constructed in recombinant E. coli, resulting in the production of 1.06 g L −1 mevalonate with a productivity of 0.03 g L −1 h −1 in a 5-L bioreactor. The mevalonate concentration and productivity were significantly enhanced with increased cell density during 2-stage aerobic fermentation, reaching 7.85 g L −1 and 0.13 g L −1 h −1, respectively. Fed-batch fermentation was further optimized under anaerobic and microaerobic conditions, and mevalonate concentrations reached 3.05 g L −1 and 4.97 g L −1, respectively, indicating that the oxygen supply exerts a large impact on mevalonate production from acetate. This study describes a method with high potential to produce mevalonate with the engineered E. coli strain XU143 using the less costly alternative feedstock acetate as a carbon source.